2013
DOI: 10.1155/2013/259256
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Migration Driven by Galectin-3 Occurs through Distinct Mechanisms Involving Selective Interactions with the Extracellular Matrix

Abstract: Monocyte migration into tissues, an important event in inflammation, requires an intricate interplay between determinants on cell surfaces and extracellular matrix (ECM). Galectin-3 is able to modulate cell-ECM interactions and is an important mediator of inflammation. In this study, we sought to investigate whether interactions established between galectin-3 and ECM glycoproteins are involved in monocyte migration, given that the mechanisms by which monocytes move across the endothelium and through the extrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Several lines of evidence have pointed to the relevance of galectin-3 in cell adhesion and motility 27,28 . This possibility was tested in HTR-8/SVneo cells using cell adhesion and migration assays (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of evidence have pointed to the relevance of galectin-3 in cell adhesion and motility 27,28 . This possibility was tested in HTR-8/SVneo cells using cell adhesion and migration assays (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Galectin‐3 has been implicated in a variety of physiological and pathological processes. In inflammation, galectin‐3 has evolved as an important regulatory mediator, shown by its capacity to promote cell adhesion, enhance phagocytosis, and induce production of NADPH‐oxidase‐derived ROS in human neutrophils …”
Section: Introductionmentioning
confidence: 99%
“…In vitro, galectin-3 induces the expression of L-selectin and IL-8 by neutrophils, suggesting that it can modulate neutrophil migration and activation (Nieminen et al, 2005). Galectin-3 is also involved in the recruitment of monocytes/macrophages from the blood stream to the inflamed tissue through interactions with laminin and fibronectin, but the underlying mechanisms are not fully understood (Danella Polli et al, 2013). Studies with different inflammation models have revealed that the lack of galectin-3 decreases the mobilization and activation of neutrophils and macrophages in tissues, with consequent reduction in the expression of pro-inflammatory cytokines and chemokines (Alves et al, 2010(Alves et al, , 2012Brand et al, 2012;Nieminen et al, 2005;Rotshenker et al, 2008;Sano et al, 2003).…”
Section: Introductionmentioning
confidence: 99%